MODEL OF DETERMINING SUPPLIERS OF FASHION PRODUCTS IN 4TH PARTY LOGISTIC ENVIRONMENT BY CONSIDERING PRODUCT QUALITY AND SUPPLIER PERFORMANCE - Thresia T, Yoan
The Micro, Small, and Medium Enterprises (MSMEs) of the fashion industry have become a concern in Indonesia due to their rapid development and impact on the Indonesian economy. Demand prediction is an important process in production planning in every industry. In the fashion industry, most researchers focus on predicting aggregate demand for one type of product. The surge in demand for basic apparel products at certain times, especially for e-commerce products, is one of the foundations for the need to predict demand. Demand precision is needed to determine the right policy. This research predicts demand by considering the quality of basic apparel products by developing an Artificial Neural Network (ANN) model. The ANN model shows good results and can be applied to estimate product demand. The Fourth Party Logistics (4PL) company is a service provider for other companies to manage logistics processes, including supplier selection issues. Supplier selection is an important process in supply chain management. In the 4PL environment, it is necessary to pay attention to the impact of determining suppliers on production capacity in the next period. This is because 4PL companies do not have their own resources and depend on other resources. Determination of suppliers by considering product quality can be a solution to maintain a better distribution of performance between suppliers. This research considers the integration of perspectives between suppliers, 4PL companies, and trademark parties so that the proposed solution considers product quality and supplier performance as a long-term decision orientation. Many research that address the issue of supplier selection have been carried out with different approaches, methods, criteria, and areas of application. Supplier selection criteria play an important role in supplier selection. The selection of criteria and sub-criteria in this research is based on the 4PL environmental perspective. This research conducted a literature research, interviews with experts, and a questionnaire survey as a method of collecting data on criteria and sub- criteria. Determination of the hierarchical structure of the criteria and sub-criteria for supplier selection is done through a literature review and the modified Delphi method. Then the Analytical Hierarchy Process (AHP) is applied to determine the weight of each criterion and sub-criteria in the hierarchical structure. In this research, the results of the ANN and AHP models serve as the basis for designing a supplier selection model. This research develops a simple multi-purpose mathematical model by considering product quality, supplier performance, and 4PL decisions oriented to the next period in a 4PL environment. The search for mathematical model solutions was carried out using the LINGO 18.0 software. The results of this research can be used as a reference in the selection of suppliers who consider the quality of basic apparel products, thus helping in making decisions in choosing the right supplier based on the perspective of the basic apparel fashion MSME industry in the 4PL environment. Through this research, the results of the distribution of performance between suppliers tend to be more even than the general determination system. With a more even distribution, it is hoped that each supplier will tend to be more committed to working with 4PL parties.